2001
DOI: 10.1046/j.1365-2540.2001.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Aedes albopictus from La Réunion Island (Indian Ocean) with respect to susceptibility to a dengue virus

Abstract: Ten F 1 Aedes albopictus samples collected from Re union Island in the Indian Ocean were tested for oral susceptibility to dengue 2 virus and 20 were analysed for genetic polymorphism by starch gel electrophoresis. Data from infection rates de®ned two distinct geographical areas: east coast vs. west coast. Genetic dierentiation was found to be dependent on ecological factors and the biological characteristics of Ae. albopictus. These results have implications for the vector ecology and pattern of migration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 26 publications
2
52
1
4
Order By: Relevance
“…À la Réunion, il a été démontré que les populations d'Ae. albopictus étaient fortement structurées notamment en fonction de facteurs environnementaux tels que la pluviométrie qui conditionne la disponibilité en eau et, par voie de consé-quence, la dispersion des moustiques et les flux de gènes (Paupy et al, 2001). L'implication d'Ae.…”
Section: Les Vecteursunclassified
See 2 more Smart Citations
“…À la Réunion, il a été démontré que les populations d'Ae. albopictus étaient fortement structurées notamment en fonction de facteurs environnementaux tels que la pluviométrie qui conditionne la disponibilité en eau et, par voie de consé-quence, la dispersion des moustiques et les flux de gènes (Paupy et al, 2001). L'implication d'Ae.…”
Section: Les Vecteursunclassified
“…albopictus originaire du SOOI pour le CHIKV n'avait jusqu'à présent jamais été évaluée, des résul-tats concernant la dengue étaient quant à eux disponibles. Des études ont démontré que des populations vectorielles originaires de la Réunion (Paupy et al, 2001) et de Madagascar (Vazeille et al, 2001) présen-taient une réceptivité orale vis-à-vis de la dengue supé-rieure à celle des populations en provenance d'Asie du Sud-Est (Vazeille et al, 2003). Tout comme pour le CHIKV, des variations de compétence vectorielle sont observées pour les DENV en fonction de l'origine géographique d'Ae.…”
unclassified
See 1 more Smart Citation
“…On the other hand, it has been reported that this species is a primary vector of DENV in situations where Ae. aegypti is rare or absent (Paupy et al 2001;Effler et al 2005;Almeida et al 2005). Therefore, in the contemporary, Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Ae. albopictus is often viewed as insignificant with respect to dengue but, already in 1977, there was a major outbreak of dengue-2 attributed to this vector on the island of Reunion affecting 30-35% of the inhabitants (Paupy et al, 2001). Between September 2001 and April 2002, 1,644 people on Hawaii were suspected of dengue infection with 122 confirmed cases at the same time as it was shown that the city of Nahiku in Hawaii, had a dense population of Ae.…”
Section: Introductionmentioning
confidence: 99%